1995
DOI: 10.1128/jb.177.16.4587-4592.1995
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic inactivation of fumarate reductase from Escherichia coli by mutation of the [3Fe-4S]-quinone binding domain

Abstract: Fumarate reductase from Escherichia coli functions both as an anaerobic fumarate reductase and as an aerobic succinate dehydrogenase. A site-directed mutation of E. coli fumarate reductase in which FrdB Pro-159 was replaced with a glutamine or histidine residue was constructed and overexpressed in a strain of E. coli lacking a functional copy of the fumarate reductase or succinate dehydrogenase complex. The consequences of these mutations on bacterial growth, assembly of the enzyme complex, and enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…This suggests that there may be a quinol binding site (at which a semiquinol radical can be stabilized) between the hemes of NarI and the [Fe-S] clusters of NarH. It has recently been shown that in E. coli fumarate reductase, the [3Fe-4S] cluster is closely or functionally associated with a menaquinol binding site (13). In E. coli dimethyl sulfoxide reductase (DmsABC), mutants in which one of the four [4Fe-4S] clusters of the wild-type enzyme is converted to a [3Fe-4S] cluster have been generated (38).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be a quinol binding site (at which a semiquinol radical can be stabilized) between the hemes of NarI and the [Fe-S] clusters of NarH. It has recently been shown that in E. coli fumarate reductase, the [3Fe-4S] cluster is closely or functionally associated with a menaquinol binding site (13). In E. coli dimethyl sulfoxide reductase (DmsABC), mutants in which one of the four [4Fe-4S] clusters of the wild-type enzyme is converted to a [3Fe-4S] cluster have been generated (38).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the microwave power dependencies of the HOQNOposed to be associated with it [26], we recorded EPR spectra at 12 K of oxidized membranes enriched in wild-type FrdABCD treated and untreated membranes are essentially identical (Fig. 2 b).…”
Section: Protein Determination Protein Concentrations Were Esti-mentioning
confidence: 91%
“…6 shows HOQNO-binding DISCUSSION titrations for membranes from the three strains used here at a It has been previously shown that the aerobic inactivation of protein concentration of 0.32 mg ml Ϫ1 . Both the background FrdA[Gln159]BCD is almost eliminated by the MKH 2 analog membranes (HB101/pBR322) and membranes containing HOQNO [26]. The Pro159→Gln mutation is within the FR3 [Arg82]FrdC (HB101/pFRD300) bind negligible concentrations [3Fe-4S] cluster binding motif of FrdB [11,13]; this prompted of HOQNO compared to the membranes containing overexus to test if there is a conformational link between FR3 and the pressed wild-type FrdABCD (HB101/pFRD84), indicating that proposed dissociable Q B site of the enzyme.…”
Section: Protein Determination Protein Concentrations Were Esti-mentioning
confidence: 99%
See 1 more Smart Citation
“…The tetranuclear center 2 and trinuclear center 3 are supposed to be ligated by cysteine residues arranged in two clusters near the C terminus. Very likely, the trinuclear center 3 is directly involved in electron transfer to quinones, which was demonstrated by site-directed mutagenesis studies of E. coli QFR and Bacillus subtilis SQR (10,20,37).…”
mentioning
confidence: 97%